Locksmith and Security Professionals' Exam Study Guide - Phillips Bill (Mc Graw Hill, 2008)
Bill Phillips is president of the International Association of Home Safety and Security Professionals. He currently works as a security consultant and freelance writer whose articles have appeared in Consumers Digest, Crime Beat, Home Mechanix, Keynotes, The Los Angeles Times, and many other periodicals. He is the author of the “Lock” article in the World Book Encyclopedia and twelve security-related books, including McGraw-Hill's The Complete Book of Home, Site, and Office Security; The Complete Book of Locks and Locksmithing, Sixth Edition; Locksmithing; Master Locksmithing; and The Complete Book of Electronic Security.